Advice for young artists - Soth, Alec 1969- (MACK, 2024)
"Between 2022 and 2024, Alec Soth visited twenty-five undergraduate art programmes across the United States. Advice for Young Artists comprises work he made there. Its title--perhaps like the visits themselves--is misleading: rather than wisdom or guidance, Soth offers an angular and unresolved reflection on artmaking at different stages of life and the relations of photography, time, and ageing. The photographs here range from formal studies evocative of the classroom to more unruly works of self-expression. Ambiguous stagings, found forms, and lyrical portraits are interspersed with gnomic quotes and unfinished credos scrawled on Post-its. Among the students, Soth himself appears at intervals, an uncertain sage in their midst. Inspired by Walker Evans’s late Polaroids, this latest body of work reveals a new expansion of Soth’s practice and a new vantage, twenty years on from the publication of his first book. Recalling the conceit of Broken Manual, it uses an instructional format as a spurious cover for introspection and provocation. As much as a study of the experience of the young artist, this is a reckoning with the prospect of becoming an old one"--https://mackbooks.co.uk/collections/frontpage/products/advice-for-young-artists-alec-soth, accessed August 26, 2024
Inserted in book: yellow printed sheet with a "self-interview" by the photographer
Keywords: Soth, Alec -- 1969-; Geschichte 2022-2024; Fotografie; Künstler -- Motiv; Soth, Alec / 1969-; Photography, Artistic; Art students / United States / 21st century / Portraits; Artists / United States / 21st century; Art, American / 21st century; Photobooks; Bildband